Complex rehabilitation prosthetic care of a patient with maxilla and mandibular resection due to osteosarcoma - Anikó Kelemen; Péter Hermann; László Kádár (Hungarian Dental Association, 2023)
In terms of deaths caused by oropharyngeal tumors, Hungary occupies a leading position not only in Europe, but also in the world. The "epidemic" spread of pharyngeal and oral cavity cancers peaked around the 2000s. Since then statistics show a decreasing tendency, but Hungary's mortality rates are still among the highest among oropharingeal cancer patients, she treatment of head and neck tumors is very complex, wants a holistic cooperation between the experts of several specialties. Restoration after surgical resection in the area of the oral cavity is the task of a prosthodontist specialised for rehabilitation dental care. Our female patient in the case report underwent a mandibular resection due to osteosarcoma at the age of 25 in 1997. Ten years later, she underwent a mandibular resection due to another, malignant bone tumor. In 2018, she again visited the Department of Prosthodontics, Faculty of Dentistry at Semmelweis University, where, after conservative dental treatments, a complex obturator prosthesis and a lower telescopic overdenture were made for her as part of a full mouth rehabilitation. The interesting thing about the case is that the patient was diagnosed with cancer in the late 1990s, when the number of cancer cases and deaths in Hungary peaked. As is typical for osteosarcoma, the disease appeared at a young age, and thanks to the professional and timely treatment, she has been living his life free of relapses. Our patient has been under the care of the Prosthodontics Clinic of Semmelweis University for 25 years, and thanks to the professional rehabilitation prosthetic care, she wears a well-functioning prosthesis. Despite the somatic and psychological burdens, the patient, with excellent compliance throughout the treatments, is satisfied with her quality of life and lives a full life.